Transformation of Junior High School Mathematics Learning: Integration of Interactive Student Worksheet and Virtual Reality Based on Deep Learning Approach - Vita Istihapsari; Jaka Wijaya Kusuma (JTAM (Jurnal Teori dan Aplikasi Matematika), 2026)
Mathematics learning in junior high schools still faces challenges in building active student engagement, deep conceptual understanding, and the application of technology during the learning process. This study aims to describe the transformation of the implementation of mathematics learning in junior high schools through the integration of interactive Student Worksheets (LKPD) and Virtual Reality (VR) based on the Deep Learning approach. The research employed a qualitative descriptive method, with data collected through classroom observations and interviews involving four classes of grade VII students and interviews with four grade VII mathematics teachers from four different junior high schools. Before implementation, all research instruments including the interactive LKPD, VR media assisted by Artsteps, observation sheets, and interview guidelines were validated by three experts in mathematics education and educational technology, and the results were categorized as very valid. Data were analyzed using the Miles and Huberman model, consisting of four stages: data collection, data reduction, data presentation, and conclusion drawing. The result of this study is that the application of the Deep Learning approach supported by interactive LKPD and VR media received a positive response from teachers and students. Interactive LKPD and VR Media effectively support the Deep Learning stages, namely (1) Introduction of material with context, (2) In-depth presentation of material, (3) Project-based assignments, (4) Discussion and collaboration, (5) In-depth reflection, (6) Provision of constructive feedback, (7) Competency-based assessment (8) Use of technology in learning, (9) Independent learning and self-regulation, (10) Evaluation and development on an ongoing basis. The implementation of learning is in line with the principles of Deep Learning, namely knowledge connectedness, active involvement, critical and reflective thinking, problem-based learning, collaboration, and intrinsic motivation; and also in line with the Deep Learning learning experience, namely understanding, applying and reflecting. These results show that the integration of interactive LKPD and VR media can be an effective strategy to transform mathematics learning at the junior high school level.